Period Facemask, Medical Uncertainty, and Islamic Bioethics: A Maqaṣidi Ethical Assessment - Amilia, Qonita; Zayyadi, Ach. (Jurnal Pemikiran Islam, 2026)
The period facemask, commonly described as the application of menstrual blood to the face for cosmetic purposes, has gained visibility through digital beauty culture and social media circulation. This article examines the practice through Islamic bioethics and maqasid al-shari’ah, with particular attention to ḥifẓ al-nafs, ḥifẓ al-‘irḍ, maṣlaḥah, and mafsadah. The study used qualitative normative library research based on selected Qur’anic verses, scholarship on Islamic bioethics and maqāṣid al-shari’ah, medical literature on menstruation and blood-derived aesthetic procedures, and scholarship on digital beauty culture. The findings indicate that available literature does not establish the safety or cosmetic efficacy of applying untreated menstrual blood directly to facial skin. The practice also differs substantially from platelet-rich plasma treatment, which involves clinical preparation, professional supervision, and procedural standards. The analysis further indicates that the period facemask raises ethical concerns related to bodily well-being, dignity, privacy, and the circulation of intimate biological material as digital content. The article does not issue a definitive legal ruling or claim that the practice produces clinical harm in every case. It argues that ethical restraint is warranted because the claimed cosmetic benefits remain insufficiently supported, while relevant concerns related to safety and dignity remain unresolved.